Anticonvulsant Suppression of Postnatal Neurogenesis in Laboratory Animals - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The effects of phenobarbital and diazepam on cell proliferation and neurogenesis were studied in newborn rats followed for 6 months, in a study at University of Dresden, Germany; Medical University, Lublin, Poland; University Medicine Berlin, Germany; and Solvay Research Laboratories, Weesp, The Netherlands.